Uma abordagem para o ensino de frações utilizando material manipulativo baseada nos princípios da engenharia didática - Magnaguagno, Camila Gasparin (2024)
Motivated by the authors' discomfort regarding the lack of naturalness of students, from different levels of education, to resolve issues related to fractions, this work seeks to propose an approach using manipulative material to improve this context. The objective is to approach operations between fractional numbers in such a way that students understand their meaning, without the need to memorize algorithms that are sometimes confusing for them. Based on the four steps proposed in the didactic engineering methodology, a didactic sequence is developed with eight activities that use circular fractions and fractional rulers. The activities were constructed so that operations with fractions are based on the equivalence of fractions and were applied to a 6th year elementary school class. From this activity, it was possible to see an improvement in students' understanding of the content, as well as an increase in the confidence they themselves feel when working with the content. It is noteworthy that activities that deactivate students' protagonism generate some resistance initially, but that students develop their autonomy throughout the applications. Even so, the teacher's mediation is essential, both in enhancing learning and in identifying possible mistakes on the part of students.